Fractal dimension and variant anatomy of the white matter of the human cerebellar hemisperes - Maryenko, N. I.; Stepanenko, O. Yu. (Journal of Education, Health and Sport, 2017)
Introduction. Morphological changes of the cerebellar lobules are found in many congenital and acquired diseases of the cerebellum, but the information on the normal structure of the cerebellar lobules do not take into account the peculiarities of individual anatomical variability, sex and age characteristics. Aim – to investigate anatomical variability and fractal dimension of the white matter of the human cerebellar hemispheres. Material and methods. The study involved 100 cerebella of people of both sexes, who died of causes unrelated to brain pathology (20–99 years old). Parasagittal sections of the cerebellar hemispheres were investigated. Results. On parasagittal sections number of main branches of white matter is very varied and depends on peculiarities of structure of the hemispheric lobules. It was found that there is individual variability of the structure of the human cerebellar hemispheres, namely white matter branching features. We described variants of the branching of the main branches of white matter of the human cerebellar hemispheres. Fractal dimension of the white matter was determined. The white matter of the cerebellum is typical quasi-fractal structure that can be objectively described using fractal dimension. Fractal index of the white matter of the cerebellar hemispheres varies from 1.119 to 1.519; average fractal index is 1.370. Fractal analysis can be used as an objective morphometric criterion for the diagnosis of various diseases of the cerebellum and other structures of the central nervous system. Conclusions. Described variants of the cerebellar lobules and fractal dimension can be used as criteria for modern diagnostic imaging techniques for the diagnosis of various diseases of the CNS. The data can be used as the basis for atlases of serial sections of the cerebellum.